People, land, and politics : demographic developments and the transformation of Roman Italy 300 BC-AD 14 - Ligt, L. de.; Northwood, Simon. (Mnemosyne, Supplements, 2008)
Recent research has called into question the orthodox view that the last two centuries of the Roman Republic witnessed a decline of the free rural population. Yet the implications of the alternative reconstructions of Italy's demographic history that have been proposed have never been explored systematically. This volume offers a series of in-depth discussions not only of the republican manpower and census figures but also of the abundant archaeological data. It also explores the growth of cities, especially Rome, and the changing distribution of the population over the Italian landscape. On the rural side it addresses the interplay between demographic, economic, and legal developments and the background to the Gracchan land reforms. Finally it examines the political implications of demographic growth and large-scale migration to the provinces. The volume as a whole demonstrates that demography is the key to many aspects of Italy's economic, social, military, and political history.